The Impact Of MSME Waqf On Economic Recovery During The Covid-19 Pandemic: Case Study Of Global Waqf -ACT - Baitul Hamdi; Dul Candra (Jurnal Ilmiah Ekonomi Islam, 2022)
The purpose of this study was to analyze the extent to which waqf recipients felt the benefits and impacts of the MSME waqf in the context of Indonesia's economic recovery in the era of the COVID-19 pandemic. The approach to this research is descriptive qualitative with a case study strategy, primary and secondary data sources. Preliminary data can be obtained from informants directly based on interviews, while secondary data sources for writers can be obtained from journals and the ACT website. The findings in the study that MSME Waqf have a positive impact on Indonesia's economic recovery specifically for waqf recipients include increasing business, living standards and welfare of waqf recipients, opening up employment opportunities, rising relationships, and soft skills and hard skills of waqf recipients and the higher the intention to give charity and help others. Meanwhile, the impact on Indonesia's economic growth is the opening of employment opportunities because MSMEs can absorb 97% of the total existing workforce and collect up to 60.4% of the total investment. If MSMEs rise, the economy will also increase.